A triangulation method on the effectiveness of digital game-based language learning for vocabulary acquisition - Kazu, Ibrahim Yasar; Kuvvetli, Murat (Springer, 2023)
This research aimed to explore the views of 8(th) grade students on digital game-based English language learning as a foreign language (EFL). A total of 69 students between the ages of 12 and 14 participated in the study. Students' vocabulary acquisition skills were tested using a web 2.0 application called Quizziz. The study utilized a triangulation method in which the results of a quasi-experiment and the metaphorical perceptions of the learners were obtained. The results of the tests were recorded at two-week intervals, and students' reactions to the results were collected using a data collection tool. The study used a pre-test, post-test, and control group design. The experimental and control groups took a pre-test before the study began. The experimental group then practiced vocabulary using Quizziz, while the control group practiced vocabulary by memorizing it in their mother tongue. The post-test results showed significant differences between the control and experimental groups. In addition, content analysis was used to analyse the data, with metaphors being grouped and frequencies calculated. The students generally expressed positive views on digital game-based EFL, stating that it was highly successful and that in-game power-ups, competing with other students, and receiving rapid feedback improved their motivation.
Keywords: Distance learning; Games and EFL; Metaphors; Triangulation; Vocabulary acquisition